2018
DOI: 10.1186/s12968-018-0454-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative cardiovascular magnetic resonance: extracellular volume, native T1 and 18F-FDG PET/CMR imaging in patients after revascularized myocardial infarction and association with markers of myocardial damage and systemic inflammation

Abstract: BackgroundCharacterization of tissue integrity and inflammatory processes after acute myocardial infarction (AMI) using non-invasive imaging is predictive of patient outcome. Quantitative cardiovascular magnetic resonance (CMR) techniques such as native T1 and extracellular volume (ECV) mapping as well as 18F-FDG positron emission tomography (PET) imaging targeting inflammatory cell populations are gaining acceptance, but are often applied without assessing their quantitative potential. Using simultaneously ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
(38 reference statements)
0
17
0
Order By: Relevance
“…Cardiac positron emission tomography (PET) can also measure myocardial metabolic reaction kinetics through the uptake of tracers . It is able to confirm viability in suspected hibernating myocardium using glucose tracers . PET is able to detect uptake in ingressing inflammatory cells and has emerging roles in the detection of prosthetic valve endocarditis and inflammatory atherosclerotic coronary and carotid plaques .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardiac positron emission tomography (PET) can also measure myocardial metabolic reaction kinetics through the uptake of tracers . It is able to confirm viability in suspected hibernating myocardium using glucose tracers . PET is able to detect uptake in ingressing inflammatory cells and has emerging roles in the detection of prosthetic valve endocarditis and inflammatory atherosclerotic coronary and carotid plaques .…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac MR(S) and PET measure similar information with differing trade‐offs in temporal and spatial resolution. The use of both in tandem could offer complementary information …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, LGE by MRI and missing or elevated [ 18 F]FDG uptake often represent the same pathophysiological imaging targets, such as myocardial infarction or necrosis in the case of myocarditis. This might change when quantitative imaging by MRI and/or more specific tracers in PET are used …”
Section: Discussionmentioning
confidence: 99%
“…This might change when quantitative imaging by MRI and/or more specific tracers in PET are used. 20,21 Sympathetic cardiac reinnervation is a known phenomenon after cardiac transplant, which becomes assessable by orthostatic stress 5 months after transplant based on assessment of heart rate variability. 22 Further, studies have shown that possible reinnervation seems to increase over time (as shown by [ 123 I]meta-iodobenzylguanidine ([ 123 I]MIBG) uptake in scintigraphy).…”
Section: Discussionmentioning
confidence: 99%